The Understanding of Growth of Transport-Stop Node on Development Axis as Base of Development of New Strategy of Local Development - Eko Budi Santoso; Heru Purboyo; Dewi Sawitri (Jurnal Studi Pemerintahan, 2013)
Development-Axes (DA) theory , is a theory which is originally stated by Pottier (1963), and restated by Hilhorst (1972) as well as stated as an alternative growth theory (Paelinck and Nijkamp, 1975, 1978; Richardson 1978, 198, 2011) in explaining the existance of nodes or centers along development axes and the end-point cities (Richardson, 1978,1981). or prime center or growth pole (Hilhorst, 1972) connected. Some of the real evidences of the implementation are the growing of many cities along highways in America, along Grote Postweg road in Indonesia, and in many other countries. So it can be said that the theory is significance as development strategy in the world, especially in making place from transport-stop node which has role as infant settlement to be larger settlement (maybe as town or city in the future) along development axes. This paper focuses on seeking theoretical explanation as new understanding about how the the growth of transport-stop node (as one of the local nodes) along DA that is influenced by the flow of people & goods along the axis. We found that the growth cannot be explained by resource-based growth theory alone and neither other conventional theories of city growth. In fact, not all transport-stop node along DA could have same growth wheter the flow of people and goods are equal along the DA. Based on the observation and in-depth interview as well as questionaire, we found that the growth of transportstop node is initiated by the existance of transport facility or service at development axes.We also found that the growth of transport-stop node has five stages of growth and the “attractiveness” as the significant factor to the growth of transport-stop node to be lager settelement. We argue that the implication of the explanation to the policy is usefull in decentralized era in Indonesia.